Pengaruh Digital Marketing, Brand Awareness, Online Customer Review Dan Flash Sale Terhadap Minat Beli Produk Skintific di E-Commerce (Studi Kasus Pada Mahasiswa Unisma 2021-2024) - Agustyas Fadilla Wulandari; Mohammad Rizal; Tri Sugiarti Ramadhan (UNIVERSITAS ISLAM MALANG, 2026)
Abstact This study aims to analyze the influence of digital marketing, brand awareness, online customer reviews, and flash sales on purchase intention of Skintific products on e-commerce platforms. This research employs a quantitative approach with a survey method involving 103 respondents—students of the Islamic University of Malang (UNISMA) from the 2021–2024 cohort who have purchased Skintific products through e-commerce. The sampling technique used is purposive sampling, and data were analyzed using multiple linear regression through SPSS software. The results are expected to show that the four independent variables simultaneously have a significant effect on purchase intention, while digital marketing and brand awareness are the most dominant factors. The findings provide practical implications for companies to design more effective digital marketing strategies to increase consumer purchase intentions, especially among young consumers. Keywords: Digital Marketing, Brand Awareness, Online Customer Review, Flash Sale, Purchase Intention, Skintific, E-Commerce.